Contact-free operating mode in scanning microwave microscopy - Гордиенко, Ю.Е.; Ларкин, С.Ю.; Чхотуа, М.С.Е. (Radiotekhnika, 2012)
The results of straight numerical calculations that were received by using the finite element method and SHF field dependencies of spacing value along probe-object system axis for conical coaxial resonator probe were considered. The fundamental signals dependencies of spacing were also given. Small perturbation theory application area for determination of contact-free fundamental signals correlations was shown.